Las capacidades de investigación en Determinantes Sociales de la Salud de grupos registrados en Colciencias, Colombia (2012-2014). - Morales-Borrero, Carolina (Revista Facultad Nacional de Salud Pública)
Objective: to update the information obtained from the study entitled "the research capabilities on Social Determinants of Health of research groups registered in Colciencias, Colombia (2005-2012)" using the information recorded in the Scienti Colciencias platform in the period between 2013 and 2014 and the contributions from leading research groups as a source of study. Methodology: a descriptive, observational study based on information recorded in the Colciencias database of research groups and scientific production on social determinants of health, "SDH". The historical and political context affecting national health-related research was reviewed in order to identify the reasons behind the weakening of the SDH research capabilities. Results: of the 65 existing groups that are registered in the Health Sciences Program in Colciencias for 2012, 3 (4.61%) are no longer linked to Colciencias. The remaining groups produced 17 scientific papers between 2013 and 2014, 11 of which (64.7%) were written in Spanish and the remaining 6 (35.3%) in English. In general, groups continue to favor the studies on Social Determinants of Health, Health Systems and Primary Health Care; emphasis on health inequalities, stress and cancer was observed. The study of water has emerged as a key issue among health research groups, and the development of networked projects at the national level has continued. Conclusions: studies using the approach proposed by the Commission on Social Determinants of Health in 2005 are prevalent. The criteria for allocating resources to research favor groups recognized by Colciencias and with broad experience. This strengthens only a part of the field of research because it also generates inequalities between groups due to institutional and geographic location, research topics, group size and research project scope. Studies comparing research capabilities in Latin America are required, as are those explaining the predominance of topics and approaches in health research.